Nilai Karakter Kebangsaan dalam Buku Teks Bahasa Indonesia Sekolah Dasar - Subekti, Tabah; Sumarlam, Sumarlam (Universitas Muhammadiyah Magelang, 2017)
Textbook as a material for the school subject within the levels of primary and secondary education. Textbook as a school?s teaching material has a vital role in forming students? character.  This is in line with the current situation, where teaching material is needed to be investigated in terms of content, especially the content of the nationalism values.  This study aims to explain the content of the nationalism character values within a Textbook on the school subject of Indonesian Language for the primary school level.  The method used in this study is literature review and content analysis.  Literature review is done to acquire the appropriate book through the detailed and accurate searching all of the textbook.  Meanwhile, the content analysis is performed through analyzing the content of nationalism character value in the textbook for the school subject of Indonesian Language, which covers the following: (1) religiosity; (2) honesty; (3) tolerance; (4) discipline; (5) hard-work; (6) creativity; (7) self-reliance; (8) democracy; (9) curiosity;  (10) national spirits; (11) nationalism; (12) respect toward achievement; (13) friendliness/communicative value; (14) peace-loving; (15) literacy ? love of reading; (16) caring for the environment; (17) social care; and (18) responsibility.  The result of the content analysis of the Indonesian Language for the textbook for the Primary School level shows that the content for the nationalism character values in the textbook has not been fully and proportionally covered.  Besides, the content is still dominated by the aspect of knowledge and has not emphasized on the comprehension, values internationalization, and its implementation.